Magnetic field influence on the discharge parameters of two-stage gas-metal plasma source - Shariy, S.V.; Yuferov, V.B.; Shvets, M.O.; Tkachov, V.I.; Katrechko, V.V. (Вопросы атомной науки и техники, 2016)
The discharge parameters and vacuum regimes of the two-stage gas-metal plasma source are presented for three
configurations of magnetic field. Distributions of deposited flows, current and voltage characteristics of the
discharge, current characteristics for reflective electrodes and target are presented. Discharge voltage is 30…150 V,
discharge current is up to 25 A. The gas discharge is initiated on air. Vapors of copper were used for discharges in
metal. The evaporation rates of copper are obtained at the level of 20…30 g/h. The results of study have shown that
mass distribution of flows deposited on the vacuum chamber walls significant deviated from Knudsen-Lamberg`s
law described of evaporation in vacuum. Представлены разрядные параметры и режимы горения вакуумной дуги двухступенчатого источника
газометаллической плазмы для трёх конфигураций магнитного поля. Приведены распределения осаждаемых
потоков, токовые и вольт-амперные характеристики разряда, токовые характеристики для электродов
отражательного разряда и мишени. Напряжение разряда 30…150 В, разрядные токи до 25 А. В газовом
разряде напускался воздух, для разрядов в парах металла использовалась медь. Полученные скорости
испарения меди находятся на уровне 20…30 г/ч. Исследования показали существенное отклонение
распределения осаждаемых потоков на стенки вакуумной камеры от закона Кнудсена-Ламберга,
описывающего испарение в вакууме. Наведені розрядні параметри та режими горіння вакуумної дуги двоступеневого джерела газометалевої
плазми для трьох конфігурацій магнітного поля. Наведено розподіл осаджуванних потоків, струмові і вольт-
амперні характеристики розряду, струмові характеристики для електродів відбивного розряду та мішені.
Напруга розряду 30…150 В, розрядні струми до 25 А. У газовому розряді напускали повітря, для розрядів у
парах металу використовувалася мідь. Отримані швидкості випаровування міді знаходяться на рівні
20…30 г/год. Дослідження показали істотне відхилення розподілу осаджуваних потоків на стінки вакуумної
камери від закону Кнудсена Ламберг, що описує випаровування у вакуумі.